Performance analysis of audio streaming over lightning-interfered MIMO channels - Ahmad, Mohd Riduan; Mohd Esa, Mona Riza; Cooray, Vernon; Dutkiewicz, Eryk (2012)
This paper evaluates the interference from lightning flashes on the quality of audio streaming transmission over MIMO wireless system operating at 2.4 GHz. A consecutive lost datagram (CLD) measurement method was used to evaluate the transmission quality during 3 heavy thunderstorms on January 25, March 17, and March 20, 2011. In addition, CLD measurements also were done on January 21 and March 30, 2011 under fair weather (FW) conditions providing a baseline for comparison. We infer that lightning interfered with the transmitted digital pulses which resulted in a higher recorded number of lost packets per burst. We found the audio streaming quality is degraded significantly during all thunderstorms.